PENGARUH NEED TO BELONG TERHADAP FEAR OF MISSING OUT PADA REMAJA AKHIR - Putri, Natasya; Utami, Rahayu Hardianti (CV. Causalita Dynamic Solutions, 2023)
Need to belong is a situation where individuals have a sense of belonging and ownership, in this case is a need for late adolescents in their social sphere. Fear of Missing Out (FoMO) is a situation where someone feels afraid of being left behind with the latest information from other people or their social environment. This research aims to determine the influence of Need To Belong on Fear of Missing Out (FoMO) in Late Adolescents. The research method used was quantitative with a total of 398 participants aged 18-21 years in Padang City. The research uses the need to belong scale from Shodiq et al., (2020) which is a scale created by Nisrina Farahana Salsabila Wibowo and Mohammad Gilang Santika which was derived from aspects of the need to belong by Baumeister and Leary which were then adapted to the research. The FoMO scale used in this research uses the Fear of Missing Out scale created by Przybylski et al., (2013) which was then adapted from Se'u & Rahayu (2022) and adapted to the research. The data analysis technique used in this research is a simple regression test to see the influence between variables. The results obtained from this research are that there is a significant influence between the two variables, getting an F value of 45.188 and a P value of 0.000 (P<0.05). These results show that the need to belong has an effect on FoMO. Apart from that, the coefficient of determination (R²) is 0.102.